The Dunn Worry Questionnaire and the Paranoia Worries Questionnaire: new assessments of worry. Issue 5 (5th April 2020) - Freeman, Daniel; Bird, Jessica C.; Loe, Bao S.; Kingdon, David; Startup, Helen; Clark, David M.; Ehlers, Anke; Černis, Emma; Wingham, Gail; Evans, Nicole; Lister, Rachel; Pugh, Katherine; et al.
Abstract: Background: The cognitive process of worry, which keeps negative thoughts in mind and elaborates the content, contributes to the occurrence of many mental health disorders. Our principal aim was to develop a straightforward measure of general problematic worry suitable for research and clinical treatment. Our secondary aim was to develop a measure of problematic worry specifically concerning paranoid fears. Methods: An item pool concerning worry in the past month was evaluated in 250 non-clinical individuals and 50 patients with psychosis in a worry treatment trial. Exploratory factor analysis and item response theory (IRT) informed the selection of scale items. IRT analyses were repeated with the scales administered to 273 non-clinical individuals, 79 patients with psychosis and 93 patients with social anxiety disorder. Other clinical measures were administered to assess concurrent validity. Test-retest reliability was assessed with 75 participants. Sensitivity to change was assessed with 43 patients with psychosis. Results: A 10-item general worry scale (Dunn Worry Questionnaire; DWQ) and a five-item paranoia worry scale (Paranoia Worries Questionnaire; PWQ) were developed. All items were highly discriminative (DWQ a = 1.98–5.03; PWQ a = 4.10–10.7), indicating small increases in latent worry lead to a high probability of item endorsement. The DWQ was highly informative across a wide range of the worry distribution, whilst the PWQ had greatest precision at clinical levels of paranoia worry. The scales demonstrated excellent internal reliability, test-retest reliability, concurrent validity and sensitivity to change. Conclusions: The new measures of general problematic worry and worry about paranoid fears have excellent psychometric properties.